Gambaran Karakteristik Pasien Covid-19 dengan Komorbid Penyakit Paru Kronik di Rumah Sakit Umum Daerah Jawa Barat - Pahmi Firman Fauzi Pahmi; Titik Respati; Ariko Rahmat Putra (Bandung Conference Series: Medical Science, 2023)
Abstract. Until now, the prevalence of COVID-19 in West Java, especially Indonesia, continues to increase. The COVID-19 pandemic has had an impact on the quality of life for the community, especially for groups with comorbid chronic lung disease. Overexpression of ACE 2 in comorbid chronic lung disease contributes to the occurrence of infection with SARS-CoV-2 up to 5 times. This research method was carried out using observational analysis with cross sectional type with total sampling and sampling technique using purposive sampling. Data on COVID-19 patients with comorbid Chronic Pulmonary Disease were obtained for 119 patients taken from medical record data at the West Java Regional General Hospital in 2020-2022. The results showed that the majority were aged 41–60 years (52.1%), women (59.7%), duration of hospitalization lasted <14 days (74.8%), and comorbid chronic lung disease most commonly occurred in pneumonia patients. chronic (84%). In conclusion, COVID-19 patients at the West Java Regional General Hospital were aged 41–60 years, women, length of stay <14 days, and the most common comorbidities were pneumonia. COVID-19 patients with comorbidities need attention, medical rehabilitation, and follow-up to prevent a series of Long COVID-19 symptoms. Abstrak. Sampai saat ini prevalensi kejadian COVID-19 di Jawa Barat terutama Indonesia terus mengalami peningkatan. Pandemik COVID-19 memberikan dampak kualitas kehidupan pada masyarakat terutama pada kelompok yang memiliki komorbid penyakit paru kronik. Ekspresi ACE 2 berlebih pada komorbid penyakit paru kronik berkontribusi untuk terjadinya terinfeksi SARS-CoV-2 sampai 5 kali lipat. Metode penelitian ini dilakukan menggunakan analisis observasional jenis cross sectional dengan total sampling dan teknik pengambilan sampel menggunakan purposive sampling. Diperoleh data pasien COVID-19 dengan komorbid Penyakit Paru Kronik sebanyak 119 pasien yang diambil dari data rekam medis di Rumah Sakit Umum Daerah Jawa Barat pada tahun 2020-2022. Hasil penelitian menunjukkan bahwa mayoritas berusia 41–60 tahun (52,1%), perempuan (59,7%), durasi rawat inap berlangsung <14 hari (74,8%), dan komorbid penyakit paru kronik paling banyak terjadi pada pasien pneumonia kronik (84%). Kesimpulannya pasien COVID-19 di Rumah Sakit Umum Daerah Jawa Barat adalah berusia 41–60 tahun, perempuan, lama rawat <14 hari, dan komorbid paling banyak pneumonia. Pasien COVID-19 dengan komorbid perlu diperhatikan, rehabilitasi medis, dan ditindaklanjuti untuk mencegah terjadi serangkaian gejala Long COVID-19.